2016
DOI: 10.1186/s40064-016-2913-y
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylactic reactions presenting with hypertension

Abstract: BackgroundAlthough a few case reports about hypertensive anaphylaxis (HA) are available in the present literature, there is no study about the prevalence of HA. In this study, we review our cases with anaphylaxis presenting with hypertension and ascertain its prevalence. The documents of the patients who had anaphylactic reactions after the procedures performed for the diagnosis and treatment of allergic diseases in GATA Haydarpasa Clinic of Allergy and Immunology between January 2010 and December 2014 were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…Hypertensive anaphylaxis has been reported previously by Solmazgul et al [4]. Evidence demonstrates that internal compensatory vasopressor mechanisms are activated within minutes of anaphylaxis development, resulting in the release of endogenous vasoactive Fig.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Hypertensive anaphylaxis has been reported previously by Solmazgul et al [4]. Evidence demonstrates that internal compensatory vasopressor mechanisms are activated within minutes of anaphylaxis development, resulting in the release of endogenous vasoactive Fig.…”
Section: Discussionmentioning
confidence: 63%
“…At this patient's presentation, the recorded high blood pressure could be due to preexisting hypertension, anxiety leading to sympathetic activation, or both. Anaphylaxis-induced high blood pressure is another rare possibility [4]. The sympathetic activation in anxiety may have increased her blood pressure from baseline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BP increased until anaphylaxis treatment was administered and transiently increased after AD injection; however, BP improved approximately 30 minutes thereafter. Although there are a few case reports about HA [ 3 , 13 ], it may occur in anaphylaxis induced by an allergen and not only in Moderna COVID-19 vaccination. It was reported that the rate of HA among anaphylaxis patients was 12.9%.…”
Section: Discussionmentioning
confidence: 99%